Credibility Without Rules - Cottarelli, Carlo (Occasional Papers; Occasional Paper ;, 1997)
During the last 25 years, monetary practice in most countries has increasingly been characterized by the attempt to achieve credibility of purpose while expanding the freedom of monetary authorities in controlling policy instruments. Thus, the world has moved toward monetary frameworks in which, through appropriate institutional devices, a better trade-off between credibility of goals and flexibility of instruments could be achieved. This attempt, surveyed in this paper, has taken many forms, depending on the countries economic, institutional, and cultural specificities.